2013
DOI: 10.1289/ehp.1306560
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Stress and Effects of Prenatal Air Pollution on Offspring Mental Health Outcomes in Mice

Abstract: Background: Low socioeconomic status is consistently associated with reduced physical and mental health, but the mechanisms remain unclear. Increased levels of urban air pollutants interacting with parental stress have been proposed to explain health disparities in respiratory disease, but the impact of such interactions on mental health is unknown.Objectives: We aimed to determine whether prenatal air pollution exposure and stress during pregnancy act synergistically on offspring to induce a neuroinflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(126 citation statements)
references
References 57 publications
11
113
0
2
Order By: Relevance
“…They also found that the same behavior was observed in rats with raphe nucleus damage. In addition, male offspring of dams that experienced both PM exposure and nest material restriction (stress) displayed increased anxiety (Bolton et al, 2013). The results of the present study are compatible with, and supported by, those of the previous studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…They also found that the same behavior was observed in rats with raphe nucleus damage. In addition, male offspring of dams that experienced both PM exposure and nest material restriction (stress) displayed increased anxiety (Bolton et al, 2013). The results of the present study are compatible with, and supported by, those of the previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, epidemiological studies suggested that pre-and post-natal exposure to traffic air pollutants, including high concentrations of particulate matter (PM), could increase susceptibility for the onset of neurodevelopmental disorders (Becerra et al, 2013;Kalkbrenner et al, 2015). Animal research also demonstrated that in utero exposure to both PM and stress induced anxietylike behavior and impaired cognition of male offspring (Bolton et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of early-life (prenatal as well as postnatal) stress on emotional and social behaviors have been a subject of several recent reviews (eg, Sandi and Haller, 2015;Nishi et al, 2014). Here, we summarize in Table form the consequences of chronic early-life adversity provoked by abnormal maternal care in the limited bedding-nesting environment (Gilles et al, 1996;Molet et al, 2014), a model recently adopted and adapted by over 50 laboratories around the world (eg, Raineki et al, 2010;Wang et al, 2011;Bolton et al, 2013;Machado et al, 2013;Maniam et al, 2014;Kohl et al, 2015;Naninck et al, 2015; Table 1). …”
Section: Emotional and Social Consequences Of Early-life Experience Vmentioning
confidence: 99%
“…La dégradation de la qualité de l'alimentation dans les pays déve-loppé et la contamination de notre environnement par des perturbateurs endocriniens sont les facteurs les plus souvent incriminés pour comprendre l'épidémie actuelle d'obésité et de maladies métaboliques. Cependant, l'exposition chronique à la pollution atmosphérique pourrait aussi jouer un rôle, comme le suggère en particulier une étude chez la souris qui montre que l'exposition foetale à des gaz d'échappement diesel augmente la réponse post-natale à un régime obésogène, avec des effets qui varient selon le sexe de l'individu (Bolton et al 2012, Bolton et al 2013). …”
Section: Discussion Et Conclusionunclassified